Morphology evolution and nanostructure of chemical looping transition metal oxide materials upon redox processes. (1st February 2017) - Qin, Lang; Cheng, Zhuo; Guo, Mengqing; Fan, Jonathan A.; Fan, Liang-Shih
Abstract: Transition metal are heavily used in chemical looping technologies because of their high oxygen carrying capacity and high thermal reactivity. These oxygen activities result in the oxide formation and oxygen vacancy formation that affect the nanoscale crystal phase and morphology within these materials and their subsequent bulk chemical behavior. In this study, two selected earlier transition metals manganese and cobalt as well as two selected later transition metals copper and nickel that are important to chemical looping reactions are investigated when they undergo cyclic redox reactions. We found Co microparticles exhibited increased CoO impurity presence when oxidized to Co3 O4 upon cyclic oxidation; CuO redox cycles prefer to be limited to a reduced form of Cu2 O and an oxidized form of CuO; Mn microparticles were oxidized to a mixed phases of MnO and Mn3 O4, which causes delamination during oxidation. For Ni microparticles, a dense surface were observed during the redox reaction. The atomistic thermodynamics methods and density functional theory (DFT) calculations are carried out to elucidate the effect of oxygen dissociation and migration on the morphological evolution of nanostructures during the redox processes. Our results indicate that the earlier transition metals (Mn and Co) tend to have stronger interaction with O2 than the later transition metals (Ni and Cu). Also, our modified Brønsted−Evans−Polanyi (BEP) relationship for reaction energies and total reaction barriers reveals that reactions of earlier transition metals are more exergonic and have lower oxygen dissociation barriers than those of later transition metals. In addition, it was found that for these transition metal oxides the oxygen vacancy formation energies increase with the depth. The oxide in the higher oxidation state of transition metal has lower vacancy formation energy, which can facilitate forming the defective nanostructures. The fundamental understanding of these metal oxide reactions is essential to designing the metal oxide-based oxygen carriers for chemical looping applications. Graphical abstract: Image 1